2012
DOI: 10.2139/ssrn.2254454
|View full text |Cite
|
Sign up to set email alerts
|

Home Computers and Child Outcomes: Short-Term Impacts from a Randomized Experiment in Peru

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 17 publications
1
28
0
Order By: Relevance
“…Berry (2012) compared two incentive treatments but did not include a pure control group. Banerjee, Banerji, Duflo, Glennerster, and Khemani (2010) report results for binary indicators of learning outcomes, whereas the outcome measures in several papers did not include language or mathematics (Beuermann, Cristia, Cruz-Aguayo, Cueto, & Malamud, 2012;Clarke et al, 2008;Kvalsvig, Cooppan, & Connolly, 1991;Lien et al, 2009;Newman et al, 2002;Seshadri & Gopaldas, 1989).…”
Section: Criteria For Study Inclusion and Exclusionmentioning
confidence: 99%
“…Berry (2012) compared two incentive treatments but did not include a pure control group. Banerjee, Banerji, Duflo, Glennerster, and Khemani (2010) report results for binary indicators of learning outcomes, whereas the outcome measures in several papers did not include language or mathematics (Beuermann, Cristia, Cruz-Aguayo, Cueto, & Malamud, 2012;Clarke et al, 2008;Kvalsvig, Cooppan, & Connolly, 1991;Lien et al, 2009;Newman et al, 2002;Seshadri & Gopaldas, 1989).…”
Section: Criteria For Study Inclusion and Exclusionmentioning
confidence: 99%
“…The authors explained that these outcomes resulted from the lack of teacher training, education resources and connectivity, which impeded the program's ability to achieve its potential for school performance. In another study regarding the same OLPC program in Peru, Beuermann et al () focused on the program's effects on the students who were able to take their computer home after class. Through the use of a randomized experiment, they found that the students who used the computers at home were more likely to perform home duties but less likely to spend time reading books.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bauernschuster, Falck and Woessmann (2014) use German data to examine the effects of broadband Internet access on children's extra-curricular school activities such as sports, music, arts, and drama and do not find evidence of crowd out. Finally, Beuermann et al (2012), using data from Peru's randomization across and within schools, do not find evidence of spillovers to classmates and friends (though close friends appear to become more proficient at using a laptop).…”
Section: Effects On Computer Skills and Other Outcomesmentioning
confidence: 82%
“…Fairlie and Robinson (2013) and Fairlie (2015) find no evidence of heterogeneous treatment effects by pre-treatment academic achievement, parental supervision, propensity for non-game use, grade, race, or gender. Beuermann et al (2012) find some evidence of a larger reduction in school effort for younger Peruvian children, but essentially no difference in effects on cognitive skills for younger children and no difference in effects on school effort and cognitive skills by gender. In their study of Romanian schoolchildren, Malumud and Pop-Eleches (2010) do not find evidence of differential effects by gender, but do find that younger children 42 experience larger gains in cognitive skills.…”
mentioning
confidence: 75%
See 1 more Smart Citation